Pemberdayaan UMKM Keripik Melalui Pelatihan Digital Marketing di Desa Kasomalang Kulon, Kecamatan Kasomalang, Kabupaten Subang - Irwan Chairuddin; Juliater Simarmata; Olfebri Olfebri; Aang Gunawan; Amrulloh Ibnu Kholdun (Jurnal Pelayanan Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting community economic growth; however, they still face various challenges in digital marketing. The problems encountered by chip-producing MSMEs in Kasomalang Kulon Village, Kasomalang District, Subang Regency include limited understanding of digital marketing, underutilization of social media as a promotional tool, insufficient skills in creating digital marketing content, the absence of a well-planned branding strategy, and limited market reach. This Community Service Program (PkM) aimed to improve the digital literacy of MSME owners, enhance their ability to use social media for business promotion, develop their digital content creation skills, expand market reach, and increase business competitiveness. The program was conducted offline through socialization, training sessions, interactive discussions, and hands-on practice on April 17, 2026, at Kasomalang Kulon Tourism Village, Subang Regency. The results indicated an improvement in participants’ understanding of digital marketing concepts, the effective use of social media for product promotion, techniques for creating attractive product photos and videos, and the importance of branding in business development. In addition, participants gained insights into digital marketing strategies that can be utilized to expand the market reach of their chip products. The program had a positive impact on strengthening the capacity of MSME owners to develop more competitive businesses, adapt to technological advancements, and pursue sustainable market expansion.